Conditional Release for Convictors of Narcotics Crimes From The Perspective of Indonesian Criminal Law - Henny Saida Flora; Henry Aspan (Human Rights et Justicia, 2025)
Parole is one of the rights of prisoners granted for the purpose of social development and reintegration, as stipulated in the Indonesian correctional system. However, granting parole to prisoners convicted of drug offenses remains controversial, given that drug offenses are categorized as extraordinary crimes with far-reaching impacts on society and the nation's future generations. This study aims to analyze the legal provisions for parole for prisoners convicted of drug offenses and their implementation from the perspective of Indonesian criminal law. The research method used is normative legal research with both legislative and conceptual approaches. The results indicate that parole for prisoners convicted of drug offenses is regulated in the Corrections Law and its implementing regulations, with stricter requirements than for prisoners convicted of general crimes, particularly regarding sentence length, behavioral assessment, and the obligation to participate in rehabilitation and correctional programs. However, in practice, obstacles remain, including differences in interpretation, weak oversight, and public concerns about the potential for recidivism. Therefore, regulatory strengthening, procedural transparency, and optimized oversight are needed to ensure that the implementation of parole for prisoners convicted of drug offenses balances the objectives of punishment, legal certainty, and a sense of public justice. [Pembebasan bersyarat merupakan salah satu hak narapidana yang diberikan dalam rangka pembinaan dan reintegrasi sosial sebagaimana diatur dalam sistem pemasyarakatan di Indonesia. Namun, pemberian pembebasan bersyarat kepada narapidana tindak pidana narkotika masih menimbulkan kontroversi, mengingat tindak pidana narkotika dikategorikan sebagai kejahatan luar biasa yang memiliki dampak luas terhadap masyarakat serta masa depan generasi bangsa. Penelitian ini bertujuan untuk menganalisis pengaturan hukum mengenai pembebasan bersyarat bagi narapidana tindak pidana narkotika serta pelaksanaannya dalam perspektif hukum pidana Indonesia. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan peraturan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa pembebasan bersyarat bagi narapidana tindak pidana narkotika telah diatur dalam Undang-Undang Pemasyarakatan beserta peraturan pelaksanaannya, dengan persyaratan yang lebih ketat dibandingkan dengan narapidana tindak pidana umum, khususnya terkait dengan lamanya masa pidana yang telah dijalani, penilaian perilaku, serta kewajiban mengikuti program rehabilitasi dan pembinaan. Namun demikian, dalam praktiknya masih terdapat berbagai kendala, antara lain perbedaan penafsiran, lemahnya pengawasan, serta kekhawatiran masyarakat terhadap potensi residivisme. Oleh karena itu, diperlukan penguatan regulasi, transparansi prosedural, dan optimalisasi pengawasan guna memastikan bahwa pelaksanaan pembebasan bersyarat bagi narapidana tindak pidana narkotika dapat menyeimbangkan tujuan pemidanaan, kepastian hukum, dan rasa keadilan masyarakat.]